Pengaruh Disiplin Kerja Terhadap Kinerja Pegawai Di Kantor Komisi Pemilihan Umum Daerah Provinsi Sulawesi Tengah - Tenggelina, Magfirah Septiani; Mufti, Muhammad Irfan; Erdiansyah (JPS: Journal of Publicness Studies, 2025)
This study aims to determine the influence of work discipline on employee performance at the General Election Commission of Central Sulawesi Province simultaneously and to measure the extent of this influence. Employee absenteeism rates in 2023 indicated variations in the number of employees who were absent, on leave, or sick. This research employs a quantitative approach, utilizing a survey method. The data used in this study consists of both primary and secondary data. The sampling technique applied is a census or saturated sampling, resulting in a total of 66 respondents. For data analysis, this study employs IBM SPSS Statistics 29. The results of this study indicate that work discipline has a positive and significant effect on employee performance at the General Election Commission of Central Sulawesi Province. The work discipline variables—adherence to time regulations, adherence to workplace behavior rules, adherence to task execution rules, and compliance with organizational regulations—simultaneously influence employee performance. This is evidenced by an F-statistic value of 248.538 with a significance level of 0.001. The coefficient of determination (R²) is 0.795, meaning that 79.5% of employee performance is influenced by work discipline, while the remaining 20.5% is affected by other factors not examined in this study.